Wireless Pulse Wave Monitoring System Based on Reflective Flexible Probe and AFE4490 - Yan HANG; Lin HUANG; Yanan LIU; Haijun WEI; Jilun YE; Xu ZHANG; Chunsheng LIU; Fan WANG (Zhongguo yiliao qixie zazhi)
Pulse rate and blood oxygen levels are crucial physiological parameters that reflect physiological and pathological information within the human body. The system designs a wireless pulse wave monitoring system utilizing a flexible reflective probe and the AFE4490, which is capable of monitoring pulse wave and blood oxygen levels on the human forehead. The system is predominantly based on a reflective flexible probe, the AFE4490, a power supply module, a control microcontroller unit (MCU), and a Wi-Fi module. Post-processing by a slave computer, the collected pulse wave data is wirelessly transmitted to a smartphone. The real-time pulse waveform, pulse rate, and blood oxygen levels are displayed on an application. Following relevant tests and verifications, the system can accurately detect pulse wave signals, meet the requirements for wearable technology, and possesses significant market application potential.